Application of Function Analysis using Function Analysis System Technique (FAST) Diagram on Taman Sari Apartment Construction Project - I Gede Angga Diputera (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Construction projects require costs as a very important element in their implementation. There are several alternative methods that can be used as a rationale for conducting studies on cost savings. One of the alternatives that can be used for savings by eliminating unnecessary costs so that the value of the project can be reduced is Value Engineering (value engineering). One of the important stages in VE is the analysis of functions whose purpose is to identify the functions that are most beneficial for the study of VE. The method used in the analysis of this function is the Function Analysis System Technique (FAST) Diagram with the aim of defining the function of each work item analyzed and can review the basic functions that are used as guidelines in the selection of alternative designs for cost savings. In the Taman Sari Apartment construction project, a function analysis was carried out on high-value work items, namely structural work, frame work, door and window leaves, wall work, floor work and roof covering work. On the work of the structure identified the basic function of the work of the structure is to plan an alternative design with outputs in order to obtain cost efficiency. Then in the work of the frame, door leaves and windows have the basic function of planning an alternative design with output to be able to provide space access. Wall work with basic functions as a room divider to provide comfort and privacy as the resulting output. In floor work with the basic function of closing the floor base and the output is to beautify the room. For roof covering work has a basic function by calculating the roof load and output to obtain cost efficiency. After the implementation of the functioning analysis stage, cost savings are carried out by identifying and reducing unnecessary costs without reducing the quality and function level of the project it self.